Improving employee performance at traditional jamu centers in madura in the era of industrial revolution 4.0 - Alvin Arifin; Hidayat, Rachmad; Hadiyati, Ernani; Suswati, Endang (Nusantara Journal of Multidisciplinary Science, 2024)
This research aimed to investigate the effects of leadership style and empowerment on job satisfaction and performance in Madura's traditional jamu centres. The study employed a questionnaire to collect data from 69 workers. The findings, with T-Statistics (3.755) > T-Table (1.96), demonstrated that leadership style had a favourable and substantial impact on performance. However, according to T-Statistics (0.843) < T-Table (1.96), leadership style did not significantly impact satisfaction. T-Statistics (11.138) exceeded T-Table (1.96), suggesting a significant and positive influence of empowerment on performance. T-Statistics (1.167) revealed that empowerment had no discernible impact on commitment. < T-Table 1.96. T-Statistics (3.459) > T-Table (1.96) indicates a positive and significant relationship between job satisfaction and performance. Job satisfaction was a major mediating factor in the effect of empowerment on performance, but it was not a mediating factor in the impact of leadership style on performance. Madura's traditional jamu centres could benefit from this research by selecting a leadership style and giving their staff more authority.